2019
DOI: 10.1007/s10549-019-05463-x
|View full text |Cite
|
Sign up to set email alerts
|

Microtubule-associated tumor suppressors as prognostic biomarkers in breast cancer

Abstract: Breast cancer is the most common malignancy in women worldwide. Although important therapeutic progress was achieved over the past decade, this disease remains a public health problem. In the light of precision medicine, the identification of new prognostic biomarkers in breast cancer is urgently needed to stratify populations of patients with poor clinical outcome who may benefit from new personalized therapies. The microtubule cytoskeleton plays a pivotal role in essential cellular functions and is an intere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 56 publications
1
14
0
Order By: Relevance
“…Together these data support a mechanism by which ATIP3 deficiency may induce a conformational change of growing microtubule ends to facilitate paclitaxel binding to the lattice, thereby sensitizing cancer cells to the anti-migratory effects of low doses of chemotherapy. This raises the interesting possibility that high levels of EB1 in ATIP3-low breast tumors may be associated with higher sensitivity to anti-migratory effects of paclitaxel, in line with our recent studies showing that combinatorial expression of ATIP3 and EB1 is a prognostic biomarker of breast cancer patient survival 29,30 .…”
Section: Discussionsupporting
confidence: 72%
“…Together these data support a mechanism by which ATIP3 deficiency may induce a conformational change of growing microtubule ends to facilitate paclitaxel binding to the lattice, thereby sensitizing cancer cells to the anti-migratory effects of low doses of chemotherapy. This raises the interesting possibility that high levels of EB1 in ATIP3-low breast tumors may be associated with higher sensitivity to anti-migratory effects of paclitaxel, in line with our recent studies showing that combinatorial expression of ATIP3 and EB1 is a prognostic biomarker of breast cancer patient survival 29,30 .…”
Section: Discussionsupporting
confidence: 72%
“…Functional studies mentioned above [ 49 , 50 ] showing that ATIP3 antagonizes the effects of EB1 on microtubule dynamics, raised the possibility that tumors with low ATIP3 and high EB1 levels may be associated with increased malignancy and worse prognosis compared with other breast tumors. Studies conducted on 5 independent cohorts of breast cancer patients indeed confirmed the increased prognostic value of combined ATIP3/EB1 expression compared with each biomarker alone [ 22 , 70 ].…”
Section: Atip3 Is a Prognostic Biomarker In Breast Cancermentioning
confidence: 93%
“…In adherent MDA-MB-231 cells grown on the RPM for 24–72 h microtubules were disorganized, with a more evident thickening in perinuclear position, whereas in MCS cells, the tubulin network was completely disrupted showing a slight diffuse fluorescence throughout the entire cytoplasm [ 49 ]. Considering that microtubule-associated tumor suppressors (such as breast cancer 1, BRCA1) can have major impact on cancer aggressiveness and clinical outcome [ 75 ], microtubule rearrangement through s-µ g can indeed be a tool to influence the latter.…”
Section: Breast Cancer Cells Exposed To Microgravitymentioning
confidence: 99%